(untitled) (Al-Qamar, 2022)
Islam does not support the plurality of wives nor put restrictions on the conduction of polygamy. In other words, Islam never prohibits them from making polygamy if certain conditions are fulfilled which mainly Quran asks for making priorities regarding polygamy widowed, and divorced women should be there to select. It could have been prohibited like other pre-Islamic practices, such as gambling, adultery, fornication, drinking, etc. However, as a way of life that takes apprehension of the natural impulse of humankind, This paper seeks to elucidate how Islam ensures that polygamy means protecting the rights and well-being of women, by making them proud of their union with a lawful husband. To avoid being in a relationship as a mistress or concubine, who is solely responsible for single parenthood, and to overcome the increasing number of divorces in some societies today, Islam ameliorates the plight of women as a result of disparity in a man-to-woman ratio by offering a solution that alleviates a woman’s status from being a mere object or commodity in the hands of men. A number of Quranic verses and Exegete’s opinions are quoted and analyzed to identify the objective and wisdom behind the permissibility of polygamy. I have also discussed in detail the reasons that summarize men involved in the act of multiple marriages. All the sexual desires of both men and women are the same and both genders seek pleasure and convention, yet the necessity, important benefits, and hazards have also been discussed. Moreover, here the evils that have crept into society through this act can be renowned, has also been suggested in this paper.